2009
DOI: 10.1021/om900458e
|View full text |Cite
|
Sign up to set email alerts
|

Development of Rhenium Catalysts for Amine Borane Dehydrocoupling and Transfer Hydrogenation of Olefins

Abstract: Five-coordinated rhenium(I) hydride complexes of the type [Re(Br)(H)(NO)(PR3)2] (R = Cy 2a, iPr 2b) were prepared from [Re(Br)2(NO)(PR3)2(η2-H2)] (R = Cy 1a, iPr 1b) via deprotonation of the η2-H2 ligands with various bases. Filling the vacant site of 2a or 2b by various less bulky two-electron donors produced the 18-electron complexes [Re(Br)(H)(NO)(PR3)2(L)] (L = O2 3, CH2CH2 4, acetylene 5, H2 6, CO 7, CH3CN 8). The influence of the trans-coordinated ligand on the Re−H bond was examined. The 1H NMR chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 25 publications
2
91
0
3
Order By: Relevance
“…Considering the manifold dehydrogenation products of AB, all the reactions were carried out with in situ NMR measurements under approximate pseudo-first-order conditions for AB with the imines in excess (0.5 mmol of 1 a reacting with 0.1 mmol of AB). According to the kinetic conversion chart based on 11 B NMR (Figure 1), the rate constants k were simulated and the DKIE values obtained [Eq. (1)].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the manifold dehydrogenation products of AB, all the reactions were carried out with in situ NMR measurements under approximate pseudo-first-order conditions for AB with the imines in excess (0.5 mmol of 1 a reacting with 0.1 mmol of AB). According to the kinetic conversion chart based on 11 B NMR (Figure 1), the rate constants k were simulated and the DKIE values obtained [Eq. (1)].…”
Section: Methodsmentioning
confidence: 99%
“…In recent studies, it was demonstrated that rhenium catalysts can promote multistep transfer hydrogenations of olefins using AB and dimethylamine borane as a polar hydrogen donor. [11] Herein, we investigate the direct reaction between imines and AB, and reach the conclusion that concerted polar double H transfers are involved.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10] More recently, the range of metal complexes reported to be capable of catalytically dehydrogenating amine-boranes has been significantly expanded. For example, homogeneous systems based on Rh, [11] Ru, [12,13] Re, [14] Ni [15,16] and Ir [17][18][19] are now known, along with those based on Group 2 and 4 metals, [20][21][22][23][24][25] and systems based on p-block metals. [26] In addition, photoactivated catalysts of the first-row transition metals have also recently been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The mixing of 2, 3 or 4 with a slight excess of either 5 or 6 in 1,2-dichlorobenzene at room temperature afforded no reaction as evidenced by 29 Si and 119 Sn NMR spectroscopy. [56,57] These combinations of Lewis acids and bases were therefore deemed appropriate for use in the FLP activation of amine and phosphane-borane adducts.…”
Section: Reactions Of Trialkyl Group 14 Triflates With Lewis Basesmentioning
confidence: 99%
“…Support for the former deduction was provided by the absence from the 13 C{ 1 H} NMR spectrum of a signal that would be considered characteristic of a two-coordinate carbon atom (δ = 213.2 ppm). [58] Further evidence for the latter can be taken from the resonance at δ = -6.2 ppm in the 29 Si{ 1 H} NMR spectrum. The 19 F NMR spectrum indicated the inclusion of the triflate ion in the product by the presence of a singlet at δ = 78.2 ppm.…”
Section: Reactions Of Trialkyl Group 14 Triflates With Lewis Basesmentioning
confidence: 99%